2023
DOI: 10.31004/cendekia.v7i2.2380
|View full text |Cite
|
Sign up to set email alerts
|

Kemampuan Numerasi Siswa dalam Menyelesaikan Soal Geometri pada Asesmen Kompetensi Minimum

Abstract: Asesmen Kompetensi Minimum (AKM) dimaksudkan menilai kemampuan kognitif siswa, salah satunya kemampuan numerasi. Sementara berdasarkan hasil PISA 2018 tingkat kemampuan numerasi di Indonesia masih tergolong cukup rendah. Metode kualitatif deskriptif diterapkan pada penelitian ini yang memiliki tujuan menganalisis kemampuan numerasi siswa dalam menyelesaikan soal geometri pada asesmen kompetensi minimum. Subjek penelitian ini ialah 21 siswa kelas XI IPA 2 di SMAN 1 Karangjati. Tes, wawancara, dan dokumentasi me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
1
3
0
4
Order By: Relevance
“…Research conducted by Naufal et al (2020) found that 46.6% of junior high school students still have difficulty understanding geometry. This is in line with research conducted by Ali & Ni'mah (2023) which states that students' geometric abilities are low. The low mastery of geometry material is because it is difficult for students to understand, and many students do not master geometry concepts (Fauzi & Arisetyawan, 2020).…”
Section: Introductionsupporting
confidence: 92%
“…Research conducted by Naufal et al (2020) found that 46.6% of junior high school students still have difficulty understanding geometry. This is in line with research conducted by Ali & Ni'mah (2023) which states that students' geometric abilities are low. The low mastery of geometry material is because it is difficult for students to understand, and many students do not master geometry concepts (Fauzi & Arisetyawan, 2020).…”
Section: Introductionsupporting
confidence: 92%
“…Literasi bahasa ini difokuskan pada kemampuan siswa untuk memahami, mengevaluasi, dan merefleksikan teks terhadap pertanyaan yang diajukan sehingga memancing siswa untuk dapat berpikir kritis (Din, 2020;Linanda & Hendriawan, 2022). Selain itu, ada juga literasi numerasi di mana menurut Ekowati et al, (2019) digambarkan sebagai kemampuan seseorang untuk merumuskan, menerapkan, dan menafsirkan matematika berbagai konteks, termasuk kemampuan melakukan penalaran secara matematis, dan menggunakan konsep, prosedur dan fakta untuk menggambarkan, menjelaskan atau memperkirakan fenomena atau kejadian (Cahyanovianty & Wahidin, 2021).…”
Section: Resultsunclassified
“…However, there are 4 students who have reached the exposing indicator and answered correctly, referred to in Figure 2. Research conducted by Cahyanovianty & Wahidin (2021) shows that grade VIII students do not understand much about AKM, so they have difficulty in the process of working on it and also have difficulty solving problems in the description section due to lack of understanding, so they are unable to answer optimally.…”
Section: Discussionmentioning
confidence: 99%